Electrochemical mineralization of cephalexin using a conductive diamond anode: A mechanistic and toxicity investigation - Coledam, Douglas A. C.; Pupo, Marilia M. S.; Silva, Bianca F. [UNESP]; Silva, Adilson J.; Eguiluz, Katlin I. B.; Salazar-Banda, Giancarlo R.; Aquino, Jose M. (Elsevier B.V., 2017)
The contamination of surface and ground water by antibiotics is of significant importance due to their potential chronic toxic effects to the aquatic and human lives. Thus, in this work, the electrochemical oxidation of cephalexin (CEX) was carried out in a one compartment filter-press flow cell using a boron doped diamond (BDD) electrode as anode. During the electrolysis, the investigated variables were: supporting electrolyte (Na2SO4, NaCI, NaNO3, and Na2CO3) at constant ionic strength (0.1 M), pH (3, 7,10, and without control), and current density (5, 10 and 20 mA cm(-2)). The oxidation and mineralization of CEX were assessed by high performance liquid chromatography, coupled to mass spectrometry and total organic carbon. The oxidation process of CEX was dependent on the type of electrolyte and, on pH of the solution due to the distinct oxidant species electrogenerated; however, the conversion of CEX and its hydroxylated intermediates to CO2 depends only on their diffusion to the surface of the BDD. In the final stages of electrolysis, an accumulation of recalcitrant oxamic and oxalic carboxylic acids, was detected. Finally, the growth inhibition assay with Escherichia coli cells showed that the toxicity of CEX solution decreased along the electrochemical treatment due to the rupture of the (i-lactam ring of the antibiotic. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Boron-doped diamond; Hydroxylation reactions; Diffusion controlled process; Escherichia coli; Toxicity assays